An Analysis Of Leading And Potential Sectors In The Development Of Archipelagic Areas (A Case Study in East Seram Regency, Maluku) - Untung F Rumau; Hendri D Hahury; Ali Tutupoho; Fredy H Louhenapessy; Fibryano Saptenno (Trunojoyo University of Madura, 2022)
This study aims to understand leading and potential sectors in the development of archipelagic area. This study used time-series data obtained from Statistics Indonesia in the form of Gross Regional Domestic Product (GRDP) of East Seram Regency, Maluku Province with location quotient and shift share at the analysis tools. The results show that East Seram Regency has 4 basic sectors – including agricultural, forestry and fisheries; mining and quarrying; real estate; and health service and social activity – in addition to 13 non basic sectors. Meanwhile, the economic sectors which have the potential to grow faster and are specialized include the agriculture, forestry and fisheries; mining and quarrying; processing industry, electricity and gas supply; water supply, sewerage, waste and recycling management; construction; wholesale and retail trade, and car and motorcycle repairs; provision of accommodation and food and beverages; information and communication; financial and insurance service; real estate; corporate service; public administration, and defense and compulsory social security; education service; health service and social activity; and other services. Further, the differential shift components which are found to be positive and growing faster compared to the GRDP of Maluku Province consist of the agriculture, forestry and fisheries; wholesale and retail trade, and car and motorcycle repairs; transportation and warehousing; provision of accommodation and food and beverages; financial and insurance service; and real estate. Furthermore, the development pattern in East Seram Regency still adopts the development pattern in continental areas as evidenced by the economic sectors in the marine and waters whose potential have not been fully utilized.